The ice extrusion test: a novel test setup for the investigation of ice-structure interaction – results and validation. (7th January 2021) - Herrnring, Hauke; Kubiczek, Jan M.; Ehlers, Sören
ABSTRACT: Understanding ice-structure interaction is critical for an efficient and safe design of offshore structures and ships in ice-covered waters. During the last decades a variety of field experiments, full-scale measurements on ships and laboratory tests have been conducted. Within this paper, a novel experimental setup of the ice extrusion test for the investigation crushing loads is proposed. Due to the flexible design of the experiment brittle and ductile ice loads can be investigated in the laboratory at different load levels. A comprehensive test series with more than 350 tests has been carried out to investigate the system behaviour. The failure mode of the ice is mostly determined by the test speed. The ratio of gap height and sample diameter is the most important parameter for the load level. A validation against full-scale data showed that with this experimental setup it is possible to generate relevant nominal local ice pressures.